2009
DOI: 10.1890/08-1025.1
|View full text |Cite
|
Sign up to set email alerts
|

Opposing assembly mechanisms in a Neotropical dry forest: implications for phylogenetic and functional community ecology

Abstract: Abstract. Species diversity is promoted and maintained by ecological and evolutionary processes operating on species attributes through space and time. The degree to which variability in species function regulates distribution and promotes coexistence of species has been debated. Previous work has attempted to quantify the relative importance of species function by using phylogenetic relatedness as a proxy for functional similarity. The key assumption of this approach is that function is phylogenetically conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

42
419
2
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 316 publications
(477 citation statements)
references
References 63 publications
42
419
2
8
Order By: Relevance
“…When we considered the functional evenness and mean nearest neighbor distance of individual traits, we found that not all traits are behaving similarly, as has been noted in previous tropical tree research comparing multivariate and individual trait dispersion patterns (e.g., Kraft et al 2008;Swenson and Enquist 2009). Specifically, wood density and leaf area showed higher functional evenness and mean nearest neighbor distance than expected, indicating a thinning of individuals with similar wood density and leaf area values.…”
Section: Changes In the Assemblage Of Functional Diversity During Thesupporting
confidence: 62%
See 2 more Smart Citations
“…When we considered the functional evenness and mean nearest neighbor distance of individual traits, we found that not all traits are behaving similarly, as has been noted in previous tropical tree research comparing multivariate and individual trait dispersion patterns (e.g., Kraft et al 2008;Swenson and Enquist 2009). Specifically, wood density and leaf area showed higher functional evenness and mean nearest neighbor distance than expected, indicating a thinning of individuals with similar wood density and leaf area values.…”
Section: Changes In the Assemblage Of Functional Diversity During Thesupporting
confidence: 62%
“…We used the positions of species along the first two PCA axes, which together explained 51% of the total variation for the multivariate analyses. Previous research on static adult tropical tree assemblage data sets has shown that the degree of local trait diversity varies by trait, reflecting divergence and convergence operating simultaneously on the functional similarity (e.g., Swenson and Enquist 2009). Thus, we performed the univariate and multivariate analyses described below.…”
Section: Sampling and Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Prinzing and co-workers find that among plants in Europe, tolerance of extremes in soil moisture was associated with higher taxonomic levels than were those for temperature or light (Prinzing et al, 2001). Similarly, tree height and seed mass are linked to broader phylogenetic groups in comparison with other functional traits in trees (Swenson and Enquist, 2009).…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, it can identify the actually sequence divergence defining ecologically coherent units (at least in respect to one trait) rather than the taxonomic level associated with a trait. The latter has been done in some recent studies of plants due to the lack of a detailed phylogenetic tree (Prinzing et al, 2001;Swenson and Enquist, 2009). For microorganisms, however, there is an abundance of sequence data and organisms are mostly classified based on phylogeny and this can be used directly for the consenTRAIT analysis.…”
Section: Discussionmentioning
confidence: 99%